Disentangling the roles of arousal and amygdala activation in emotional declarative memory - de Voogd, Lycia D. (Soc Cogn Affect Neurosci, 2016)
A large body of evidence in animals and humans implicates the amygdala in promoting memory for arousing experiences. Although the amygdala can trigger threat-related noradrenergic-sympathetic arousal, in humans amygdala activation and noradrenergic-sympathetic arousal do not always concur. This raises the question how these two processes play a role in enhancing emotional declarative memory. This study was designed to disentangle these processes in a combined subsequent-memory/fear-conditioning paradigm with neutral items belonging to two conceptual categories as conditioned stimuli. Functional MRI, skin conductance (index of sympathetic activity), and pupil dilation (indirect index of central noradrenergic activity) were acquired throughout procedures. Recognition memory for individual items was tested 24 h later. We found that pupil dilation and skin conductance responses were higher on CS+ (associated with a shock) compared with CS− trials, irrespective of later memory for those items. By contrast, amygdala activity was only higher for CS+ items that were later confidently remembered compared with CS+ items that were later forgotten. Thus, amygdala activity and not noradrenergic-sympathetic arousal, predicted enhanced declarative item memory. This dissociation is in line with animal models stating that the amygdala integrates arousal-related neuromodulatory changes to alter mnemonic processes elsewhere in the brain.